Penerapan Metode Ruq’yah Melalui Bimbingan Rohani Islam Pada Jama’ah Majlis Ta’lim Dziqrulgofiliin Masjid At-Tawwab Brimob Simongan, Kecamatan Semarang Barat - Kibtyah, Maryatul; maydi, Rizka Azzahra (Jurusan Bimbingan dan Konseling Islam, 2024)
medical and non-medical conditions, including spiritual disturbances like ‘ain and hasad. This study examines the application of Islamic spiritual guidance through ruqyah therapy for the Jama'ah Majlis Ta'lim Dzikrulgofilin at Masjid At-Tawwab Brimob, West Semarang, and identifies its supporting and inhibiting factors. The research employs a descriptive qualitative approach, involving an ustadz (Islamic teacher) who conducts ruqyah, five congregants, and their guardians as participants. Data collection methods include observation, interviews, and documentation, with validity ensured through method and source triangulation. Data analysis follows stages of reduction, presentation, and conclusion drawing. The findings reveal that ruqyah therapy is performed monthly on Friday kliwon nights after evening prayers, guided by Islamic values and Quranic recitations. Three methods are employed: istilham, tahshin, and Al-Syarab bil Qur'an. Before therapy, congregants are advised to undergo medical examinations to identify health issues. Post-therapy, participants receive Quran-recited salt and honey as supplementary health aids. Supporting factors include family support and personal motivation for healing, while inhibiting factors are weak faith and disobedience to parents. This study highlights the integration of spiritual and physical dimensions in addressing health concerns, emphasizing the role of Islamic values in therapeutic practices and the significance of familial and personal commitment in the healing process.